One or two species? A morphometric comparison between robust australopithecines from Kromdraai and Swartkrans - Zachary Cofran; J. Francis Thackeray (South African Journal of Science)
The type specimen of Paranthropus robustus (TM 1517, including a partial cranium) was discovered at Kromdraai near Sterkfontein in 1938 and described by Robert Broom as a new species. Subsequently, more robust australopithecines were discovered at the nearby site of Swartkrans. These Swartkrans hominins were described by Broom as Paranthropus crassidens. Many palaeoanthropologists currently regard the robust australopithecines from Kromdraai and Swartkrans as one species, but consensus has not been reached on this issue. A morphometric analysis has been undertaken to assess the probability that specimens attributed to P. crassidens represent the same species as that which is represented by TM 1517, the holotype of P. robustus. Our results failed to reject the null hypothesis that both sites sample the same, single species of robust australopithecine.